Design of Single Acting Pulley Actuator (SAPA) Continuously Variable Transmission (CVT) - Priyandoko, Gigih; Cholis, N.; Ariyono, S. (Elsevier Ltd, 2015)
The design of Single Acting Pulley Actuator (SAPA) Continuously Variable Transmission (CVT) utilizes combinations of DC motor system, gear reducers and power cam mechanisms to actuate primary movable pulley sheaves on the transmission shaft. The secondary pulley supported by spring provides a belt clamping force to prevent slips, while the secondary controls the rubber v-belt from slipping. Since the methods of controlling these are similar, this paper only discusses the primary part. The servomotor regulates the axial movement of primary movable pulley sheaves to shift the rubber v-belt placed between the sheaves, and change the belt-pulley contact radius. Changing this contact radius means changing the CVT ratio. Computer simulation results are presented to demonstrate the effectiveness of the proposed PD controller. The research outcome gives a significant result to complete 75.08° rotation of the CAM from lower gear ratio to top gear ratio is less than 6.79 sec, with minimum error and less overshoot with a manual PD tuning contribution to the field of DC motor based electro-mechanical CVT control system.